2021
DOI: 10.1111/aji.13412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the menstrual cycle and ethinyl estradiol/etonogestrel contraceptive vaginal ring on granulysin and other mucosal immune mediators

Abstract: Problem: Changes in sex hormones during the menstrual cycle and contraceptive vaginal ring (CVR) use influence immunity within the female genital tract, but the magnitude of these effects and their anatomical location are unclear. Method of Study:In a prospective study, 29 women were assessed at three-time points: follicular phase, luteal phase, and one month after initiation of the ethinyl estradiol/etonogestrel CVR (NuvaRing®, Merck). We performed microarrays on endocervical cytobrushes and measured immune m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Since the expression levels of the most common endometrial receptivity genes also did not differ between the LH + 2 and LH + 7 samples, cervical cells' transcriptomics is probably unsuitable for receptivity testing. The lack of transcriptomic differences between the cervical cells collected from the follicular and luteal phase was also reported in a previous microarray study (22), which coincides our results. Our results demonstrated that the transcriptome of cervical cells is relatively uniform throughout the menstrual cycle; however, more changes occur in the latesecretory phase, when the best time for embryo implantation is already passed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since the expression levels of the most common endometrial receptivity genes also did not differ between the LH + 2 and LH + 7 samples, cervical cells' transcriptomics is probably unsuitable for receptivity testing. The lack of transcriptomic differences between the cervical cells collected from the follicular and luteal phase was also reported in a previous microarray study (22), which coincides our results. Our results demonstrated that the transcriptome of cervical cells is relatively uniform throughout the menstrual cycle; however, more changes occur in the latesecretory phase, when the best time for embryo implantation is already passed.…”
Section: Discussionsupporting
confidence: 93%
“…During the sample collection with a cervical brush, mainly superficial cells are obtained, and the most hormone sensitive glandular cells in cervical crypts are not collected, which likely explains the differences between our and previous results. Endocervical tissue (7,8) studies have reported significant gene-expression changes between proliferative and secretory phase samples, but no similar menstrual cyclerelated changes were seen in brush-derived cervical cells (22). Like endometrial tissue, endocervical tissue contains estrogen and progesterone receptors that make it susceptible to progesterone action during the menstrual cycle (23).…”
Section: Discussionmentioning
confidence: 99%
“…These results affirm data from the same cohort in which we observed that CCVR users had significantly elevated inflammatory- and Th17-related cytokine concentrations in cervicovaginal fluid (CVF) compared to COC and Net-En users and relative to baseline levels ( 5 , 9 ). Similarly, in a small prospective study of US women initiating CCVR (NuvaRing ® , Merck), the endocervical expression of immune-related genes increased after 1 month of CCVR use compared to both the follicular and luteal phase of the menstrual cycle prior to CCVR initiation ( 71 ). We further observed that CCVR users had lower levels of transcriptional responses indicative of epithelial differentiation and keratinization relative to those assigned to Net-En or COC.…”
Section: Discussionmentioning
confidence: 97%
“…We further observed that CCVR users had lower levels of transcriptional responses indicative of epithelial differentiation and keratinization relative to those assigned to Net-En or COC. While there is limited data on the effects of CCVRs on cervical gene expression, some studies have identified increased levels of genital matrix metalloproteinase (MMPs) and reduced levels of MMP tissue inhibitors (TIMPs) with CCVR initiation ( 71 ), suggestive of mucosal barrier repair or remodeling ( 18 ). Whether CCVR use mediates the disruption of epithelial barrier or whether this occurs up- or downstream of the CCVR-mediated increase in inflammation and dysbiosis observed in this cohort is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%